Prone bridge variations with and without instability devices: an electromyographical comparison - Snarr, R. L.; Esco, M. R.; Eckert, R. M. (Journal of Sport and Human Performance, 2017)
Core muscle endurance training is an important component of overall health and fitness as well as sports performance. Increasing core endurance aids in a reduction of spinal injuries, increases in power transfer from the extremities, and spinal stability. Performing exercises designed to increase core muscular activity using commercial instability devices have been gaining in popularity; however research is limited on these trending apparatuses. Therefore the objective of this research was to examine the superficial abdominal wall musculature when performing plank variations with and without instability devices. To complete this study, 12 healthy males (n = 6) and females (n = 6), mean age = 23 ± 3 years, volunteered to participate. Participants performed five prone bridge, or plank, variations using a suspension device, Swissball, or stable surface in a counter-balanced design. The five exercises are as follows: traditional plank (REG), planks with either the hands (HB) or feet (FB) placed on the Swissball (HB), and planks with either the hands (HSD) or feet (FSD) placed within a suspension device. Each plank was performed twice with the arms fully extended and was held for a 5-second isometric contraction. The electromyographical (EMG) activity of the rectus abdominis (RA), external obliques (EO), and lumbo-sacral erector spinae (LSES) was recorded for each exercise. The results indicated that significant differences existed within each of the muscles examined. HB resulted in significantly greater (p < 0.05) activation of the RA (105.03 ± 50.93 %MVC) when compared to all remaining exercises. In terms of the external obliques, the FB provided significantly greater muscle activity (84.46 ± 43.73 %MVC; p < 0.05) compared to the REG, HB, and FSD. Additionally, LSES activity was demonstrated to be significantly greater (p < 0.05) than the traditional method in both variations of the Swissball planks (i.e., HB and FB). The results of the study demonstrate that planks performed with the aid of instability devices can increase muscular activation of the core musculature. Both Swissball and suspension device planks provided a significantly greater challenge when compared to the traditional method for both the RA and EO. Therefore, instability devices may be used as a progressive challenge in rehabilitation and fitness settings to increase core muscle endurance.